Cardiac Markers in Pediatric Laboratory Medicine: Critical Review - Renata Zrinski Topic; Jasna Lenicek Krleza (Diagnostics)
Currently, there are no validated guidelines or recommendations for how to interpret cardiac biomarkers in the pediatric population. The most commonly used cardiac biomarkers are cardiac troponins and natriuretic peptides, but the clinical value of common cardiac biomarkers in pediatric laboratory medicine is restricted due to age- and sex-specific interpretations, and there are no standardized cut-off values. The results from the studies on reference values, as well as results from clinical studies, are difficult to compare with identical studies due to the heterogeneity of subject characteristics (gestational and chronological age, sex, pubertal status, menstrual cycle, exercise), assay characteristics (type of assay, generation of assay, analytical platform used), and experimental protocol characteristics (prospective or retrospective studies, reference population selection, patient population selection, inclusion and exclusion criteria, number of subjects). Future studies need to establish evidence-based cut-offs for specific indications to optimize utilization and standardize the interpretation of common cardiac biomarkers in neonates, children, and adolescents. The aim of this article was to summarize the current analytical and clinical limitations of cardiac troponins and natriuretic peptides in the pediatric population, as informed by the existing published literature.